The effects of wood extractive on the fixation and leaching of ACC preservative in Beech (Fagus orientalis Lipsky) wood - vahid reza Safdari (Regional Information Center for Science and Technology (RICeST), 2013)
Wood chemical components are among the most important and effective factors in the fixation of water-borne preservatives in the wood. This research investigated the effect of wood extractive on fixation and leaching of “arsenic copper chromate“(ACC) preservative in beech (Fagus orientalis) wood blocks. Three groups of wood blocks (control, as wood with extractive, wood pre-extracted with hot water and wood pre-extracted with ethanol acetone) were impregnated with 2% ACC and then were placed in an incubator for 0, 192, 384, 576, and 768 hours at 25 ºC and 75% humidity. After removal from the incubator, the blocks were extracted and the preservative solution of each block was analyzed. The Cr(VI) of the extracted preservative, as the indication of the fixed amount in wood was analyzed using UV spectroscopy and the Cu and Cr contents was measured by atomic absorption. The results showed that the effect of hot water-soluble extractive on fixation and leaching of ACC was significant (P